2002
DOI: 10.1194/jlr.m100438-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Serum plant sterols and biliary cholesterol secretion in humans

Abstract: Ratios of cholestanol, campesterol, and sitosterol to cholesterol in serum are known to reflect cholesterol absorption efficiency. Here, a possible link between these ratios and biliary secretion rates of cholesterol was investigated. Biliary lipid secretion rates and serum sterols were determined in 13 patients with gallstones. Seven were treated with ursodeoxycholic acid (UDCA) (1,000 mg/d). Serum cholesterol and non-cholesterol sterols were also measured in a cross over study in 20 healthy volunteers, who r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
(29 reference statements)
1
8
0
Order By: Relevance
“…Previously, it has been postulated that in selected patients ratios of serum campesterol and sitosterol to cholesterol reflect the biliary cholesterol secretion rates 43. Because in our study we used the surrogate markers for cholesterol transport and synthesis, which indicated a link between cholesterol homeostasis and GSD, we further strengthened our findings by analysis of biliary lipid compositions, demonstrating that gallstone patients display increased biliary levels of both phytosterols and cholesterol.…”
Section: Discussionsupporting
confidence: 65%
“…Previously, it has been postulated that in selected patients ratios of serum campesterol and sitosterol to cholesterol reflect the biliary cholesterol secretion rates 43. Because in our study we used the surrogate markers for cholesterol transport and synthesis, which indicated a link between cholesterol homeostasis and GSD, we further strengthened our findings by analysis of biliary lipid compositions, demonstrating that gallstone patients display increased biliary levels of both phytosterols and cholesterol.…”
Section: Discussionsupporting
confidence: 65%
“…This is supported by demonstrations that weight reduction or statin therapy decreases cholesterol synthesis and biliary cholesterol, resulting in an increase in cholesterol absorption efficiency [19,21]. A recent study [22] also showed that biliary cholesterol secretion is inversely associated with plasma plant sterol levels. In the present study, we used the campesterol : cholesterol and lathosterol : cholesterol ratios to estimate cholesterol absorption and synthesis respectively.…”
Section: Discussionmentioning
confidence: 82%
“…However, reduced desmosterol conversion would be associated with reduced levels of 3beta-hydroxysterol Delta24-reductase (DHCR24) also known as seladin-1 and increased levels of all precursors carrying a double bond at C-24 including lanosterol (Waterham et al, 2001). We also measured the levels of dihydrolanosterol, the post-lanosterol step and a lathosterol precursor (Lindenthal et al, 2002) and found no changes in ABCA1 -B/-B cortex or hippocampus (data not shown). This suggests that the increase in cholesterol precursors is not due to their decreased degradation.…”
Section: Resultsmentioning
confidence: 94%